2015
DOI: 10.1158/1541-7786.mcr-14-0372
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Tumorigenic Potential of Colorectal Cancer Cells by Extracellular Sulfatases

Abstract: Heparan sulfate endosulfatase-1 and -2 (SULF1 and SULF2) are two important extracellular 6-O-endosulfatases that remove 6-O sulfate groups of N-glucosamine along heparan sulfate (HS) proteoglycan chains often found in the extracellular matrix. The HS sulfation pattern influences signaling events at the cell surface, which are critical for interactions with growth factors and their receptors. SULFs are overexpressed in several types of human tumors, but their role in cancer is still unclear because their molecu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 51 publications
1
27
0
Order By: Relevance
“…This finding indicates that the observed modifications cannot be attributed exclusively to a depletion of SULF1 enzymatic activity, but also involves fine tuning of the HS structure through the biosynthesis machinery. Recently, a study on colorectal cancer cells over-expressing SULFs reported an increase in GlcNAc(6S)-containing disaccharides as a cellular response that compensates for the enzymatic driven decrease in [ΔUA(2S)-GlcNS(6S)] [59]. Our data support such complementary behavior, here in the context of SULF1 down-regulation by SDC1.…”
Section: Discussionsupporting
confidence: 82%
“…This finding indicates that the observed modifications cannot be attributed exclusively to a depletion of SULF1 enzymatic activity, but also involves fine tuning of the HS structure through the biosynthesis machinery. Recently, a study on colorectal cancer cells over-expressing SULFs reported an increase in GlcNAc(6S)-containing disaccharides as a cellular response that compensates for the enzymatic driven decrease in [ΔUA(2S)-GlcNS(6S)] [59]. Our data support such complementary behavior, here in the context of SULF1 down-regulation by SDC1.…”
Section: Discussionsupporting
confidence: 82%
“…HSPGs regulate signaling pathways important in cell proliferation, inflammation, angiogenesis, and invasion and are dysregulated in cancer (reviewed in (18) and (55)). As extracellular molecules, HSPGs and the extracellular enzymes that modify them, SULF2 and HPSE, are amenable to therapeutic targeting.…”
Section: Discussionmentioning
confidence: 99%
“…PC-3 cells were washed with PBS and incubated in serum free culture medium containing a blocking DNA replication mitomycin C (10 µg/L) to avoid cell proliferation. The cells were wounded using 200 µl sterile pipette tips and then washed to remove detached cells and debris (28) and incubated in the absence (control, basal level of cellular function) and presence of 17β-estradiol (E2, 0.1 and 10 nM; Sigma Chemical Co.); ERβ-selective agonist DPN [10 nM; 2,3-bis(4-hydroxyphenyl)-propionitrile, Tocris Bioscience, Bristol, United Kingdom] and ERB-041 (10 nM; Sigma Chemical Co.) or ERα-selective agonist PPT [10 nM; 4,4' ,4"-(4-propyl-(1H)-pyrazole-1,3,5-triyl)trisphenol, Tocris Bioscience] for 24 h at 37 • C. The cells were also untreated or pretreated with ERβ-selective antagonist PHTPP [10 nM; 4-(2-phenyl-5,7-bis(trifluoromethyl)pyrazolo(1,5-a)pyrimidin-3-yl)phenol, Tocris Bioscience] or with a compound that disrupts the complex β-catenin-TCF/LEF transcription factor, PKF 118-310 (100 nM, Sigma-Aldrich Co) for 30 min. Incubation was continued in the absence and presence of DPN (10 nM) or ERB-041 (10 nM), for 24 h at 37 • C (18,21,22).…”
Section: Wound Healing Analysismentioning
confidence: 99%